1977
DOI: 10.1002/art.1780200410
|View full text |Cite
|
Sign up to set email alerts
|

Cellular infiltrates in scleroderma skin

Abstract: The purpose of this study was to determine the frequency, distribution, and nature of cellular infiltrates in 108 skin biopsies from patients with systemic scleroderma (SS) and localized scleroderma (LS). Cellular infiltrates, perivascular or diffuse, were noted in 49% of SS and 84% of LS patients and consisted of lymphocytes, plasma cells, and macrophages. No correlation was noted between the presence or severity of skin cellular infiltrates and serum serologic abnormalities.Systemic scleroderma is a connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
1
3

Year Published

1977
1977
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(175 citation statements)
references
References 27 publications
7
164
1
3
Order By: Relevance
“…In early phases of SSc, there are often perivascular and/or diffuse mononuclear infiltrates that include both T cells and macrophages (27). Our observations are consistent with the findings of Fleischmajer et al in that the Siglec-1ϩ macrophages are both perivascular and located between collagen bundles in the dermis (49). Thus, Siglec-1ϩ macrophages might play an important role as effector cells in fibrosis through cytokine release.…”
Section: Discussionsupporting
confidence: 91%
“…In early phases of SSc, there are often perivascular and/or diffuse mononuclear infiltrates that include both T cells and macrophages (27). Our observations are consistent with the findings of Fleischmajer et al in that the Siglec-1ϩ macrophages are both perivascular and located between collagen bundles in the dermis (49). Thus, Siglec-1ϩ macrophages might play an important role as effector cells in fibrosis through cytokine release.…”
Section: Discussionsupporting
confidence: 91%
“…SSc patients have autoantibodies that react to various intracellular components, such as DNA topoisomerase I, centromere, RNA polymerases, U1RNP, and U3RNP (2). In addition, hypergammaglobulinemia and polyclonal B cell hyperactivity are detected in SSc patients (3,4). Furthermore, a recent study demonstrated that down-regulation of B cell function leads to improved skin fibrosis in the tight-skin mouse, a genetic model of SSc (5).…”
Section: Conclusion Ssc Patients Have Distinct Abnormalities Of Bloomentioning
confidence: 99%
“…Several lines of evidence suggest that T cells are important in the pathogenesis of SSc, including observations that ␣/␤ and ␥/␦ T lymphocytes exhibit increased expression of activation markers (3,4), show signs of antigen-driven expansion (5), and dominate the inflammatory infiltrates in the skin and involved tissues during the early stages of the disease (6,7). T cells have been found to be necessary for the production of antitopoisomerase I antibodies in SSc (8).…”
mentioning
confidence: 99%